Pola Rekrutmen KPPS dan Implikasinya Terhadap Kinerja Pemilu Serentak 2024 di Desa Gandusari, Kabupaten Trenggalek, Jawa Timur - Alfa Ridho, Syeikhu (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2025)
This study describes the recruitment pattern of the Voting Organizing Group (KPPS) and its implications for the performance of the 2024 simultaneous elections in Gandusari Village, Trenggalek Regency, East Java. The location is noteworthy due to the high demand for KPPS members, while public interest in applying remained low. These conditions prompted the Village Election Committee (PPS) to make several adjustments, such as relying on personal recommendations and reappointing former members. The analysis draws upon the theory of Proximity-Based Recruitment, which highlights the role of social networks and trust-based selection in recruitment processes, and the theory of organizational effectiveness, which evaluates performance based on efficiency, procedural compliance, and accuracy of outcomes. Employing a descriptive qualitative approach through observation, in-depth interviews, documentation, and literature review, the findings reveal that recruitment in Gandusari prioritized fulfilling the quota rather than competency-based selection. Consequently, KPPS performance was procedurally adequate but remained weak regarding efficiency, accuracy, and the sustainability of work quality.